외모 만족, 사회적 지지, 학업적 효능감의 상관관계에 관한 연구 - 김의형; Eui-hyoung Kim (한국미용학회지, 2021)
This study attempted to understand adolescents’ growth process by discovering how their appearance satisfaction, social support, and academic self-efficacy are related to each other, thereby providing basic data which can help in enhancing academic self-efficacy. In terms of the influence of appearance satisfaction on social support, the respondents who were more satisfied with their physical image and subjective appearance, perceived increased teacher support, friend support, and parental support. According to the analysis of the effects of appearance satisfaction on self-efficacy, task difficulty preference increased as subjective appearance satisfaction and physical image satisfaction improved, and the desire for appearance improvement was lower. In addition, as subjective appearance satisfaction and physical image satisfaction increased, self-regulatory efficacy improved. While subject appearance satisfaction increased and the desire for appearance improvement was lower, self-confidence improved. In terms of the influence of social support on academic self-efficacy, task difficulty preference increased as parental support and teacher support were high. As parental support and teacher support increased, self-regulatory efficacy improved. Furthermore, as parental support and friend support increased, self-confidence increased as well. The study results confirm that appearance satisfaction, social support, and academic efficacy are closely related to each other in adolescents.